Multiple coupled resonances in the human vascular tree: refining the Westerhof model of the arterial system - Schumacher, Gerhard; Kaden, Jens; Trinkmann, Frederik (Journal of applied physiology, 2017)
The human arterial vascular tree can be described by multicompartment models using electrical components. First introduced in the 1960s by Noordergraaf and Westerhof, these hardware-based approaches required several simplifications. We were able to remove the restrictions using modern software simulation tools and improve overall model quality considerably. Whereas the original Westerhof model consisted of 121 Windkessel elements, the refined model has 711 elements and gives realistic pulse waveforms of the aorta and brachial and radial arteries with realistic blood pressures. Moreover, novel insights concerning the formation of the physiological aortic-to-radial transfer function were gained. Its being potentially due to the coupling of many small resonant elements gives new impetus to the discussion of arterial pressure wave reflection. The individualized transfer function derived from our improved model incorporates distinct patient characteristics and can potentially be used for estimation of central blood pressure values.NEW & NOTEWORTHY We were able to find an individualized transfer function giving realistic pulse waveforms and blood pressures using a multicompartment model of the arterial system. Based on the hardware-built Westerhof approach, several simplifications initially introduced in the 1960s could be reversed using software simulation. Overall model quality was improved considerably, and multiple coupled resonances were identified as potential explanation for the formation of the aortic-to-radial transfer function, giving new impetus to the discussion of arterial pressure wave reflection.